OUTLOOK SALES OF SHALE OIL UNDER LOW OIL PRICES - D. K. Davudov; Sh. T. Ismailova (Вестник Дагестанского государственного технического университета: Технические науки)
In article prospects of development of the market of slate oil in the conditions of the low world prices for oil are considered. As a result of the analysis authors opened concept of slate oil, the condition of the market of slate oil is analysed, the forecast of development of the slate industry is made. During research it was proved that despite decrease in quantity of wells and investments into development of slate fields, the increase in production of slate oil due to scientific and technical progress will be observed.